Review of the Chinese species of the genus Tropidocephala Stål, 1853 (Hemiptera: Fulgoromorpha: Delphacidae), with descriptions of two new species - Sha-Sha Lv; Hong-Xing Li; Yu-Bo Zhang; Lin Yang; Xiang-Sheng Chen (European Journal of Taxonomy, 2025)
The Chinese species of the genus Tropidocephala Stål, 1853 are reviewed. 26 species are recognized, of which T. brunnipennis Signoret, 1860, T. dingi Sun, Yang & Chen, 2014, T. festiva (Distant, 1906), T. jiawenna Kuoh, 1979, T. longiapina Ding, 1982, T. nigra (Matsumura, 1900), T. serendiba (Melichar, 1903), T. sinica Ding, 2006, and T. sinuosa Yang & Yang, 1986 are illustrated and redescribed, and two new species, T. lamellata sp. nov. and T. yunnanensis sp. nov. are described and illustrated. A checklist and key of Chinese species in the genus are provided.